Uso de pistas preditivas durante a recuperação de contexto temporal - Grace Ane Morgana Cavalcante de Queiroz (2018)
Judgment of recency refers to the retrieval of temporal qualities of studied information. Previous studies pointed to the existence of two cognitive processes underlying judgments of recency. One of these processes is based on distance and intimately connected to familiarity, whereas the other is based on location, involving a more detailed recollection of the moment in which the stimulus was encoded. Several studies have already investigated this topic, however, no study has so far evaluated how external information presented at test influenced performance during judgments of recency. To investigate this, two experiments involving 40 participants each (18 to 35 years old) were conducted. In both experiments, figures of objects were presented during one of two study blocks separated by a 15 minutes interval. In experiment 1, the memory test consisted in judging whether objects (presented individually) were seen in the first or second study block. In experiment 2, the memory test consisted in judging which of two objects was last presented at study (i.e., in second block of study phase).In 80% of the trials of both memory tests, cues in the form of arrows forecasted the correct responses with 75% of accuracy. Participants made confidence ratings while responding. Cues that accurately predicted correct responses produced increased accuracy, while cues that were misleading produced decreased accuracy. Even though reaction times were influenced by cues in a manner consistent with accuracy, confidence was immune to cueing influences. Such finding suggests that accuracy and confidence are based on distinct processes, and adds evidence for the notion that confidence is an unreliable proxy for accuracy.